Visualization of phosphatidylcholine (16:0/16:0) in type II alveolar epithelial cells in the human lung using imaging mass spectrometry. (20th May 2013) - Kurabe, Nobuya; Hayasaka, Takahiro; Igarashi, Hisaki; Mori, Hiroki; Sekihara, Keigo; Tao, Hong; Yamada, Hidetaka; Kahyo, Tomoaki; Onishi, Ippei; Tsukui, Hiroe; Kawase, Akikazu; Matsuura, Shun; et al.
<x xml:space="preserve">Abstract</x> Imaging mass spectrometry (MS) is an emerging technique that can detect numerous biomolecular distributions in a non‐targeting manner. In the present study, we applied a mass imaging modality, mass microscopy, to human lung tissue and identified several molecules including surfactant constituents in a specific structure of the lung alveoli. Four peaks were identified using imaging MS, and the ion at m/z 772.5, in particular, was localized at some spots in the alveolar walls. Using an MS/MS analysis, the ion was identified as phosphatidylcholine (PC)(16:0/16:0), which is the main component of lung surfactant. In a larger magnification of the lung specimen, PC (16:0/16:0) was distributed in a mottled fashion in a section of the lung. Importantly, the distribution of PC (16:0/16:0) was identical to that of anti‐SLC34A2 antibody immunoreactivity, which is known to be a specific marker of type II alveolar epithelial cells, in the same section. Our experience suggests that imaging MS has excellent potential in human pathology research.